EFFECT OF DIFFERENT SYNGAS COMPOSITIONS ON THE COMBUSTION CHARACTERISTICS AND EMISSION OF A MODEL COMBUSTOR (Nigerian Journal of Technology, 2020)
There is a growing need to design fuel flexible combustors. This require understanding of the combustion and emission characteristics of the combustors under varying fuel compositions.  In the present study, the combustion characteristics and emission of methane and syngas flames were investigated numerically in a swirl stabilized combustor. The numerical model was developed using ANSYS-fluent software and validated using experimental values of temperature, CO2 and NOx emissions. A two-step chemical mechanism was used to model methane-air combustion. Results of the numerical validation showed similar trend between the experimental and predicted temperature along the combustor axis with about 5 % over prediction of the temperature. Syngas-air combustion was thereafter modeled using a 21 step chemical mechanism. Syngas compositions studied were: syngas A (67% CO: 33% H2), syngas B (50% CO: 50% H2) and syngas C (33% CO: 67% H2). Results showed that for pure methane, a V-shaped flame was observed with the flame attached to the fuel nozzle, while a lifted flame was observed for case of syngas A composition. CO gas with higher ignition temperature and flammability as compared to H2 gas is the dominant gas in syngas A fuel composition. Jet flames were observed for syngas B and syngas C. Carbon monoxide is a slow burning gas. Therefore syngas with low CO content has a low tendency of emission of CO from the combustor. This suggests that syngas with high CO content such syngas A may require more residence time to completely combust the CO gas. The NOx emission was observed to have the same trend as that of the combustor maximum temperature. Syngas C flame had the highest NOx emission, while, syngas A flame had no NOx emission. This is due to low combustor temperature observed in the case of syngas A flame.  http://dx.doi.org/10.4314/njt.v39i3.16